PENGARUH PEMANFAATAN GAME BLOOKET MODE FISHING FRENZY DAN LITERASI DIGITAL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MATA PELAJARAN EKONOMI KELAS X DI SMAN 3 SAMARINDA - Fristi Novianti; Margaretha Lasni Rhusarry; Umi Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology requires students to master Digital Literacy and Critical Thinking Skills, which are very important in learning Economics. This research aims to examine the influence of the Utilization of the Blooket Game Fishing Frenzy Mode and Digital Literacy, both partially and simultaneously, on the Critical Thinking Skills of Class X students at SMAN 3 Samarinda, who face the problem of conventional learning. This research, using a quantitative approach and associative research type, was conducted at SMAN 3 Samarinda, involving 68 Class X students as a sample determined through simple random sampling. Data was collected using a Likert scale questionnaire and analyzed using multiple linear regression, F-test, t-test, and the Coefficient of Determination (R2) with the aid of SPSS. The results of the research indicate that both the Utilization of Blooket and Digital Literacy have a significant partial influence on Critical Thinking Skills. Simultaneously, the two variables also have a significant influence on the dependent variable. It is concluded that the integration of Blooket as a gamification medium and the strengthening of Digital Literacy are proven to be effective and relevant in improving students' Critical Thinking Skills as an essential 21st-century competence.